Synthesis of the BEAC4ND4 Ionophore from p-t-Butylcalix[4]arene Carboxylic Acid - Nasriadi Dali; Arniah Dali; Seniwati Dali; Hilda Ayu Melvi Amalia (Jurnal Kimia Sains dan Aplikasi, 2020)
The BEAC4ND4 ionophore has been successfully synthesized from p-t-butylcalix[4]arene carboxylic acid. The BEAC4ND4 ionophore was obtained in two steps of the synthesis reaction. The first step is the chlorination reaction of p-t-butylcalix[4]arene carboxylic acid with thionyl chloride in dry benzene solvent. The chlorination reaction product is p-t-butylcalix[4]arene acyl chloride in the form of the light brown viscous liquid with a yield of 78.25% and TLC (SiO2, CH3OH: CH2Cl2 = 1: 1 v/v, Rf = 0.65). The second step is the amidation reaction of ethyl 2-aminoacetate with p-t-butylcalix[4]arene acyl chloride in dry tetrahydrofuran solvent. The product of the amidation reaction is p-t-butylcalix[4]arene ethylesteramide or the BEAC4ND4 ionophore in the form of a white solid with the yield of 75.22%, a melting point of 314-316°C, and TLC (SiO2, CH3OH: CH2Cl2 = 1: 1 v/v, Rf = 0.75).